Islamic Microfinance Service Quality and Its Impact on Yogyakarta Customers’ Satisfaction and Loyalty - Pras, Prastyono Putro Pangarso; Sumadi, Sumadi (Publisher Cv. Inara, 2020)
The purpose of this study is to examine the effect of service quality and religiosity on customer satisfaction and loyalty of Islamic Microfinance (KSPPS) in Yogyakarta. The research method uses a qualitative approach. The population in this study were all KSPPS customers in Yogyakarta. Samples were taken by 150 customers from 8 KSPPS using purposive sampling techniques. The analytical tool used for testing hypotheses in this study uses Structural Equation Model (SEM) analysis with the Analysis Moment of Structure (AMOS) software application. The results of this study indicate that customer satisfaction has a positive and significant effect on customer loyalty. Religiosity has a positive and significant effect on customer satisfaction. Religiosity has a positive but not significant effect on customer loyalty. Service Quality has a positive and significant effect on customer satisfaction. Quality of service has a positive and significant effect on customer loyalty.